The Role of The Nagari-Owned Enterprise Bukik Sakumpo in Improving Community Welfare at Nagari Pasie Laweh, Sungai Tarab District - Hanifa, Selvi; Irwandi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The main problem identified is the low and uncertain income levels in this thesis: The Role of the Bukik Sakumpoa Village-Owned Enterprise (BUMNag) in Improving the Welfare of the Pasie Laweh Village Community, Sungai Tarab District. The purpose of this discussion is to analyze the role of BUMNag and identify the obstacles faced by BUMNag Bukik Sakumpoa in improving the welfare of the Pasie Laweh Village community, Sungai Tarab District.The type of research used by the author is field research using qualitative research methods through a descriptive analysis approach to obtain data on the problems studied. The data collection techniques used by the researcher were observation, interviews, and documentation. This study utilized primary and secondary data sources. Data analysis included data collection, data reduction, data presentation, verification, and conclusion drawing. To verify the validity of the data, the researcher used triangulation of sources and techniques.From the field research, it can be concluded that State-Owned Enterprises (BUMNag) serve as a means of improving community welfare by assisting communities in meeting financial needs, developing businesses, increasing community income, improving economic well-being, and increasing Village Original Income (NPWP). The Bukik Sakumpa Village-Owned Enterprise (BUMNag) plays a crucial role in improving community welfare through various means, such as providing business capital for the community, supporting the development of MSMEs, and managing the village's economic potential. Obstacles in BUMNag management include low community participation in the BUMNag's planned community engagement programs and low community participation in purchasing necessities from the BUMNag.